2005
DOI: 10.1016/j.cep.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Separation of n-hexane–ethyl acetate mixtures by azeotropic batch distillation with heterogeneous entrainers

Abstract: Tel: (33) 5 62 88 58 26 ; fax: (33) 5 62 88 58 29Accepted for publication in Chemical Engineering & Processing Abstract.In this article, a systematic study of the separation of the n-hexane -ethyl acetate mixture with an entrainer by heterogeneous azeotropic batch distillation is performed. Based upon the thermodynamic behaviour of the ternary mixtures, potential entrainers partially miscible with one or two original azeotropic components are chosen. In all cases, the entrainer adds a heterogeneous binary or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Conventional distillation is not a suitable technique to separate ethyl acetate from hexane because of the formation of minimum azeotropic mixtures, and it is not economically feasible. Azeotropic batch distillation was used to separate this azeotrope 4 using different entrainers including water, acetonitrile, nitromethane, and methanol. 5 This technique is characterized by some setbacks which include long exposure times of the mixture to high temperatures that can result in thermal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional distillation is not a suitable technique to separate ethyl acetate from hexane because of the formation of minimum azeotropic mixtures, and it is not economically feasible. Azeotropic batch distillation was used to separate this azeotrope 4 using different entrainers including water, acetonitrile, nitromethane, and methanol. 5 This technique is characterized by some setbacks which include long exposure times of the mixture to high temperatures that can result in thermal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Batch distillation is widely used in fine chemical production such as in the pharmaceutical industry. Diwekar divided batch distillation processes into six types, one of which is called batch distillation with a middle vessel. The middle vessel batch distillation process has attracted much scholarly attention in recent years. Barolo et al found that the feed rate to the column affects the column performance, and operation at infinite reflux and reboil ratios may be more profitable.…”
Section: Introductionmentioning
confidence: 99%
“…Two simple entrainer selection rules are proposed, which make it possible to screen entrainers for heterogeneous azeotropic batch distillation with minimum efforts. Systematic study of the separation of the n-hexane-ethyl acetate mixture and another paper for the separation of tert-butyl alcohol-water mixture with an entrainer by heterogeneous azeotropic batch distillation were performed in Rodriguez-Donis et al (2005) and in Xu and Wand (2006), respectively. A general method for the calculation of residue curves and for the determination of batch distillation regions of heteroazeotropic distillation was suggested in Lang and Modla (2006).…”
Section: Introductionmentioning
confidence: 99%